ANALYSIS OF INTERFERENCE BETWEEN LTE SYSTEM AND TETRA SYSTEM IN THE 800 MHZ BAND - Natasha, Fadhilah; Usman, Uke Kurniawan; Satria, Rizky (Sekolah Tinggi Teknologi Adisutjipto, 2020)
Wireless communication is used in many sectors to support the need of communication, the example of wireless communication is applied in mission critical network. Wireless communication system that used in mission critical are Terrestrial Trunked Radio (TETRA) and Long Term Evolution (LTE). TETRA systems supports voice services while LTE supports voice and data services. Co-exsitence between LTE and TETRA in same frequency band is one of the optimilazition quality for mission critical network. For this final project analyses interference in co-exsitence between LTE and TETRA in frequency band 800 MHz. There are four scenarios using extended-hata model propagation in urban area. There are several parameters that reviewed, desired Received Signal Strength (dRSS), interfering Received Signal Strength (iRSS), Carrier to Interference ratio (C/I) and probability of interference. In all scenarios occur Co-Channel Interference (CCI) between LTE and TETRA in frequency band 800 MHz so the performance not optimal. The performance increased when add guard band variation. The variation that applied are 0,5 MHz, 0,75 MHz, 1 MHz. Based on the result of the simulation that have been done, proposed the used of guard band variation for elevate the performance.